The Conchal Cartilage Butterfly Graft - Friedman, Oren; Coblens, Orly (Facial Plastic Surgery, 2016)
Nasal obstruction due to weakening of the nasal sidewall is a very common patient complaint. The conchal cartilage butterfly graft is a proven technique for the correction of nasal valve collapse. It allows for excellent functional results, and with experience and attention to technical detail, it may also provide excellent cosmetic results. While this procedure is most useful for restoring form and function in cases of secondary rhinoplasty following the reduction of nasal support structures, we have found it to be a very powerful and satisfying technique in primary rhinoplasty as well. This article aims to describe the butterfly graft, discuss its history, and detail the technical considerations which we have found useful.
Keywords: rhinoplasty; functional rhinoplasty; nasal valve